Pengaruh medication therapy management terhadap kepatuhan pasien hipertensi tidak terkontrol - Stephany, Ni Wayan Dhea; Erwin, Tubagus; Dora, Miranti Dea (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Hypertension or high blood pressure is often referred to as the silent killer because it is often without complaints, but can cause the risk of heart disease, stroke, kidney failure. Compliance with taking medication is very important to control and support healing and prevent complications. Purpose: To determine the effect of medication therapy management (MTM) on compliance of patients with uncontrolled hypertension. Method: Quantitative research with quasi experimental research design one group pretest posttest design. The sample in this study amounted to 70 respondents with data collection techniques using non-probability sampling. The instruments used were the MTM form and the MMAS-8 questionnaire (Morisky medication adherence scale). Data analysis used univariate and bivariate analysis. Results: Univariate analysis of variable frequency distribution data showed that the majority of respondents were female, totaling 41 (58.6%) and most were aged 41-50, totaling 11 (15.7%). Bivariate analysis using the Wilcoxon Signed Ranks Test obtained a p-value of 0.000 (P <0.05). Conclusion: There is an effect of Medication Therapy Management (MTM) on the compliance of uncontrolled hypertension patients. Conclusion: There is an influence of Medication Therapy Management (MTM) on the compliance of uncontrolled hypertension patients. Keywords: Hypertension; Medication Adherence; Medication Therapy Management. Pendahuluan: Hipertensi atau tekanan darah tinggi sering disebut sebagai the silent killer karena sering tanpa keluhan, tetapi dapat menyebabkan risiko penyakit jantung, stroke, gagal ginjal. Kepatuhan minum obat sangat penting untuk mengontrol serta menunjang kesembuhan dan mencegah komplikasi. Tujuan: Untuk mengetahui pengaruh dari medication therapy management (mtm) terhadap kepatuhan pasien hipertensi tidak terkontrol Metode: Penelitian kuantitatif dengan desain penelitian quasi experimental one group pretest posttest design. Sampel dalam penelitian ini berjumlah 70 responden dengan teknik pengumpulan data menggunakan non-probability sampling. Instrumen yang digunakan yaitu formulir MTM dan kuesioner MMAS-8 (morisky medication adherence scale). Analisis data menggunakan analisis univariat dan bivariat. Hasil: Analisis univariat tentang data distribusi frekuensi variabel didapatkan hasil mayoritas responden berjenis kelamin perempuan berjumlah 41 (58,6%) dan sebagian besar berumur 41-50 sebanyak 11 (15,7%). Analisis bivariat dengan menggunakan Wilcoxon Signed Ranks Test didapatkan hasil nilai p sebesar 0,000 (P <0,05). Simpulan: Ada pengaruh Medication Therapy Management (MTM) terhadap kepatuhan pasien hipertensi tidak terkontrol. Kata Kunci: Hipertensi; Kepatuhan Minum Obat; Medication Therapy Management.